Lower IgG somatic hypermutation rates during acute dengue virus infection is compatible with a germinal center-independent B cell response. Issue 1 (December 2016) - Godoy-Lozano, Elizabeth; Téllez-Sosa, Juan; Sánchez-González, Gilberto; Sámano-Sánchez, Hugo; Aguilar-Salgado, Andrés; Salinas-Rodríguez, Aarón; Cortina-Ceballos, Bernardo; Vivanco-Cid, Héctor; Hernández-Flores, Karina; Pfaff, Jennifer; Kahle, Kristen; Doranz, Benjamin; et al.
Abstract Background The study of human B cell response to dengue virus (DENV) infection is critical to understand serotype-specific protection and the cross-reactive sub-neutralizing response. Whereas the first is beneficial and thus represents the ultimate goal of vaccination, the latter has been implicated in the development of severe disease, which occurs in a small, albeit significant, fraction of secondary DENV infections. Both primary and secondary infections are associated with the production of poly-reactive and cross-reactive IgG antibodies. Methods To gain insight into the effect of DENV infection on the B cell repertoire, we used VH region high-throughput cDNA sequencing of the peripheral blood IgG B cell compartment of 19 individuals during the acute phase of infection. For 11 individuals, a second sample obtained 6 months later was analyzed for comparison. Probabilities of sequencing antibody secreting cells or memory B cells were estimated using second-order Monte Carlo simulation. Results We found that in acute disease there is an increase in IgG B cell diversity and changes in the relative use of segmentsIGHV1-2, IGHV1-18, andIGHV1-69 . Somewhat unexpectedly, an overall low proportion of somatic hypermutated antibody genes was observed during the acute phase plasmablasts, particularly in secondary infections and those cases with more severe disease. Conclusions Our data are consistent with an innate-like antiviral recognition system mediated by B cells using defined germ-line coded B cell receptors, which could provide a rapid germinal center-independent antibody response during the early phase of infection. A model describing concurrent T-dependent and T-independent B cell responses in the context of DENV infection is proposed, which incorporates the selection of B cells using hypomutated IGHV segments and their potential role in poly/cross-reactivity. Its formal demonstration could lead to a definition of its potential implication in antibody-dependent enhancement, and may contribute to rational vaccine development efforts.